2010
DOI: 10.1002/elan.201000262
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Potentialities of Carbon Nanotube/Silicone Rubber Composite Electrodes: Determination of Propranolol

Abstract: A new composite electrode based on multiwall carbon nanotubes (MWCNT) and silicone-rubber (SR) was developed and applied to the determination of propranolol in pharmaceutical formulations. The effect of using MWCNT/ graphite mixtures in different proportions was also investigated. Cyclic voltammetry and electrochemical impedance spectroscopy were used for electrochemical characterization of different electrode compositions. Propranolol was determined using MWCNT/SR 70 % (m/m) electrodes with linear dynamic ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 42 publications
3
15
0
1
Order By: Relevance
“…26,27 Two possible mechanisms for the electrochemical oxidation of propranolol were proposed in the literature. Bishop and Hussein 28 reported that the hydroxyl group is oxidized, involving 2 protons and 2 electrons.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Two possible mechanisms for the electrochemical oxidation of propranolol were proposed in the literature. Bishop and Hussein 28 reported that the hydroxyl group is oxidized, involving 2 protons and 2 electrons.…”
Section: Resultsmentioning
confidence: 99%
“…8 shows a comparison of determination of propranolol by oxidation using cyclic, differential pulse and square-wave voltammetry and clearly demonstrates the higher sensitivity of SWV. In another example, thionine was immobilised on CNT before preparing a carbon paste electrode to measure Reproduced with permission from [237] ascorbic acid, acetaminophen and isoniazid simultaneously [238]. In these cases, it is necessary to circumvent the increased tendency for adsorption of organic compounds on the electrode surface.…”
Section: Screen-printed Electrodesmentioning
confidence: 99%
“…For pharmaceutical applications, a CNT/silicone rubber composite electrode was developed for propranolol [237]; Fig. 8 shows a comparison of determination of propranolol by oxidation using cyclic, differential pulse and square-wave voltammetry and clearly demonstrates the higher sensitivity of SWV.…”
Section: Screen-printed Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The proposed mechanism involves 2 protons and 2 electrons according to: The irreversible oxidation peak observed for metabolites of PRO could be connected with adequate mechanism of oxidation process.…”
Section: Effect Of Phmentioning
confidence: 99%